Six Multiplex TaqManTM-qPCR Assays for Quantitative Diagnostics of Pseudomonas Species Causative of Bacterial Blotch Diseases of Mushrooms - Taparia, Tanvi; Krijger, Marjon; Hodgetts, Jennifer; Hendriks, Marc; Elphinstone, John G.; van der Wolf, Jan (Frontiers in Microbiology, 2020)
Bacterial blotch is a group of economically important diseases of the common button mushroom (Agaricus bisporus). Once the pathogens are introduced to a farm, mesophilic growing conditions (that are optimum for mushroom production) result in severe and widespread secondary infections. Efficient, timely and quantitative detection of the pathogens is hence critical for the design of localized control strategies and prediction of disease risk. This study describes the development of real-time TaqManTM assays that allow molecular diagnosis of three currently prevalent bacterial blotch pathogens: ‘Pseudomonas gingeri’, Pseudomonas tolaasii and (as yet uncharacterized) Pseudomonas strains (belonging to Pseudomonas salomonii and Pseudomonas edaphica. For each pathogen, assays targeting specific DNA markers on two different loci, were developed for primary detection and secondary verification. All six developed assays showed high diagnostic specificity and sensitivity when tested against a panel of 63 Pseudomonas strains and 40 other plant pathogenic bacteria. The assays demonstrated good analytical performance indicated by linearity across calibration curve (>0.95), amplification efficiency (>90%) and magnitude of amplification signal (>2.1). The limits of detection were optimised for efficient quantification in bacterial cultures, symptomatic tissue, infected casing soil and water samples from mushroom farms. Each target assay was multiplexed with two additional assays. Xanthomonas campestris was detected as an extraction control, to account for loss of DNA during sample processing. And the total Pseudomonas population was detected, to quantify the proportion of pathogenic to beneficial Pseudomonas in the soil. This ratio is speculated to be an indicator for blotch outbreaks. The multiplexed assays were successfully validated and applied by routine testing of diseased mushrooms, peat sources, casing soils and water from commercial production units.